Location of central depots for ethanol supply chain in Thailand - Homchalee, Rojanee (Asia-Pacific Journal of Science and Technology, 2017)
In order to improve efficiency of logistics system of Thai ethanol supply chain, this study aimed to design and manage ethanol supply chain in Thailand from plants to customers, which were gasohol blending and exporting depots. Supply chain network was designed with ethanol central depots. Location-allocation model was developed to locate the central depots and allocate ethanol appropriately, with the objective to minimize total cost. Preliminary, the context of Thai ethanol supply chain was studied by literature review, secondary data collecting and interviews with relevant agencies. Consequently, supply chain structure and supply chain drivers were analyzed. Alternative ethanol central depots were determined using cluster analysis by K-means and hierarchical clustering methods. In addition, other alternative depots were defined by considering geographically possible location along transport infrastructure of the country. Afterward, all alternative depots were used to be decision variables of the model. The results showed that Thailand should have only one ethanol collection depot for export located along wharfs in Samut Prakan province. However, central depots should be located along the highway between Khon Kaen and Nakhon Ratchasima provinces in the northeast region and Nakhon Sawan province in the upper central region.